1993
DOI: 10.1161/01.cir.87.6.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disrupting the mitral apparatus on left ventricular function in dogs.

Abstract: Background. The importance of the mitral apparatus to left ventricular function has been suggested in clinical studies. The effect of disruption of the mitral apparatus on left ventricular diastolic and systolic properties has not been fully documented.Methods and Results. We investigated the end-diastolic and end-systolic pressure-volume and stroke work-end-diastolic volume relations and measured the isovolumic relaxation time constant ('r,) during nonfilling beats before and after disruption of the mitral ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…where m is the slope of the EDP-volume relationship, V is the volume, and V 0 is the balloon volume at which EDP is zero, or the x-axis intercept. 16,17 Developed pressure. Developed pressure in the left ventricle (DP) was defined as the difference between ESP and EDP for a given beat.…”
Section: Discussionmentioning
confidence: 99%
“…where m is the slope of the EDP-volume relationship, V is the volume, and V 0 is the balloon volume at which EDP is zero, or the x-axis intercept. 16,17 Developed pressure. Developed pressure in the left ventricle (DP) was defined as the difference between ESP and EDP for a given beat.…”
Section: Discussionmentioning
confidence: 99%
“…Relative conductance-derived volume changes correlated highly to relative volume changes calculated with caval flow analysis. Second, the slope of the end-systolic and end-diastolic P-V relations were fitted to a straight line, and, whereas linear fitting of the behavior of the P-V loop may not be accurate over a large range of volumes and pressures, the goal of this study was to address changes within a physiological range, where differences between linear and exponential fitting are negligible (25,32,35). Furthermore, for the left atrium, these indexes have shown sensitivity and accuracy in assessing atrial function during load manipulation and inotropic stimulation in a relatively load-independent manner (1,22).…”
Section: Potential Limitationsmentioning
confidence: 99%
“…The conventional valve-replacement technique involves excision, with concomitant loss of the continuity between the valve annulus, valve tissue, chordae, and the ventricular wall. Clinical studies have shown, however, that preservation of the subvalvular apparatus plays an important role in maintaining ventricular performance after valve replacement [David 1983;Hennein 1990;Ghosh 1992]. Besides, the long-term outcome in corrected transposition of the great arteries is mainly determined by the function of the systemic ventricle, and consideration should be given to replacing the systemic atrioventricular valve at the earliest signs of progressive ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%